A Perspective on the Doctrine of the Separation of Powers Based on the Response to Court Orders in Kenya (Strathmore Law Review, 2016)
The Constitution of Kenya provides that the sovereign power of the people shall be vested in the executive, the legislature and the judiciary, reflecting the democratic ideal that if power is concentrated in the hands of a few, it is prone to misuse. This provision aims to safeguard against arbitrary and capricious governance and the abuse of power. In the new constitutional order, there has been instances of tensions between the judiciary and the other arms of government. Unfortunate incidents of members of the Legislature referring to court orders as stupid and idiotic with blatant disregard for court orders have been witnessed. In a government whose legitimacy is vindicated by a court, it is ironical to observe a selective attitude towards respecting subsequent court orders. This paper aims to consider the disregard of court orders against the backdrop of the separation of powers and other relevant principles of constitutionalism.